Potential Of Endophytic Bacteria From Papaya (Carica Papaya) To Control Colletotrichum Gloeosporioides - Zainal, Tengku Siti Nor Zaimas Tengku (2012)
Current approaches to control papaya disease rely on the use of chemicals fungicide which is detrimental to human health and environment. Thus, there is a need to find and develop biological means of controlling pathogens of papaya. One of the most serious threats to papaya crop is anthracnose disease caused by Colletotrichum gloeosporioides. This study was conducted to investigate the potential of endophytic bacteria from Carica papaya as biological control agents against anthracnose by in vitro means. A total of 47 and 57 bacterial endophytes were isolated from fruits and leaves of papaya, respectively. The endophytic bacteria were identified based on their morphological and physiological characteristics, BIOLOG Identification System, and 16S rDNA sequence analysis. Based on the results, both strains F21 and L63 were identified as Bacillus species. These Bacillus spp. successfully showed inhibitory effects against C. gloeosporioides isolates 1 and 2. Based on dual culture test, Bacillus sp. L63 has the potential to be biocontrol agent against C. gloeosporiroides isolates 1 and 2 with percentage of inhibition 47.05% and 58.06%, respectively. Severe morphological changes were observed on the fungal mycelia when treated with Bacillus sp. L63. In conclusion, Bacillus sp. L63 has the potential to serve as biological control agents against C. gloeosporioides.